2022
DOI: 10.1200/jco.2022.40.16_suppl.e16196
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor DNA is a potential prognostic risk factor of recurrence in patients with hepatocellular carcinoma treated by liver transplantation.

Abstract: e16196 Background: Liver transplantation (LT) is one of the most effective therapeutic strategies for hepatocellular carcinoma (HCC), however, tumour recurrence after LT often leads to poor outcomes. At present, clinical characteristic profile, imaging diagnosis as well as level of serum biomarkers prior to LT could predict the prognosis in HCC patients treated by LT. However, the sensitivity and specificity of these biomarkers are limited, highlighting the crucial need to identify novel biomarkers. Previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Another study, performed on ten patients, found a complete correlation between ctDNA detection and the recurrence of HCC [85]. Jiang et al, in a study with 45 HCC patients, found the same correlation, with an increased recurrence rate for patients with detectable ctDNA (48.6% vs. 0%) [86].…”
Section: Quantitativementioning
confidence: 81%
“…Another study, performed on ten patients, found a complete correlation between ctDNA detection and the recurrence of HCC [85]. Jiang et al, in a study with 45 HCC patients, found the same correlation, with an increased recurrence rate for patients with detectable ctDNA (48.6% vs. 0%) [86].…”
Section: Quantitativementioning
confidence: 81%
“…In HCC, Wang et al (2020) showed a reduced RFS with post-operative ctDNA assessed according to a panel of four hotspot genomic mutations in TP53 (G747T), CTNNB1 (A121G, C133T), and TERT (c.-124C>T) [ 30 ]. In the setting of liver transplant for unresectable primary liver cancer, larger scale studies by Huang et al (2023) [ 23 ] and Jiang et al (2022) [ 31 ] again display higher recurrence rates in patients with positive post-transplant ctDNA and decreased disease-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…At a minimum, pre- and post-LT testing should be pursued when using tissue-agnostic testing in order to obtain a pre-transplant comparison. With expanding evidence supporting the use of ctDNA testing in liver cancers [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ], the optimization of protocols effective at addressing the concerns regarding donor-derived alterations is warranted in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…They noted that clinical factors such as BCLC stage, maximum tumor diameter, and serum AFP were ineffective predictors of disease-free and overall survival. However, patients with detectable ctDNA experienced a significantly increased recurrence rate and diminished median disease-free survival [32]. All these studies showed that CTC and ctDNA correlated very well with the risk of recurrence and survival.…”
Section: Pushing the Limit Of Predicting Post-transplantation Survivalmentioning
confidence: 93%
“…However, patients with detectable ctDNA experienced a significantly increased recurrence rate and diminished median DFS. 32 All these studies showed that CTC and ctDNA correlated very well with the risk of recurrence and survival. Further studies on the CTC, ctDNA, or other molecular biology markers represent a novel strategy to measure tumor burden.…”
Section: Predicting Post-transplantation Survival: To Prioritize Utilitymentioning
confidence: 96%